2013
DOI: 10.2478/s11756-013-0250-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tillage on soil macropore size, shape of top layer and crop development in a sub-humid environment

Abstract: Topsoil macropores of two plots under no-tillage and conventional tillage were analyzed. A leguminous-cereal rotation was applied for six cycles under dry-land farming system (crop residues were removed). The clay-loam soil shows some vertic characteristics. The main goal is to identify the relationship between the top soil macro and meso-pore distribution for the two tillage systems (at the end of sixth cycle of cultivation) with the annual crop production (rainfall in normal growing period and crop productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…In fact, macroporosity was significantly higher in CT (10.8%) than in NT (6.1% p < .02) and microporosity significantly lower ( p < .01), being macroporosity 25% of total porosity in CT and 14% in NT. In this respect, Josa, Gorchs, Ginovart, and Solé‐Benet () indicated higher presence of macropores in CT compared with NT. Similarly, Shipitalo and Protz () indicated that no‐till plots had approximately half the macroporosity of those of conventionally tilled plots.…”
Section: Resultsmentioning
confidence: 95%
“…In fact, macroporosity was significantly higher in CT (10.8%) than in NT (6.1% p < .02) and microporosity significantly lower ( p < .01), being macroporosity 25% of total porosity in CT and 14% in NT. In this respect, Josa, Gorchs, Ginovart, and Solé‐Benet () indicated higher presence of macropores in CT compared with NT. Similarly, Shipitalo and Protz () indicated that no‐till plots had approximately half the macroporosity of those of conventionally tilled plots.…”
Section: Resultsmentioning
confidence: 95%
“…Mangalassery et al (2014) found larger differences between ZT and CT, with CT porosity 47% higher than under ZT soils in the upper 10 cm when assessed by X-ray micro Computed Tomography (μCT) at a resolution of 64 μm. An increased number of macropores in CT compared to ZT in the surface but a higher proportion of micropores in ZT soils has been reported by Josa et al (2013) and Mangalassery et al (2014). Previously, most studies have focused on agricultural land under ZT management for ten years or fewer, with long-term studies typically viewed as those with 5 years beyond conversion.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the different outcome in our case is not clear; however, a possible explanation could lie in the specific weather conditions in 2015, which resulted in exceptionally dry topsoil conditions before the spring tillage and throughout the season. Soil moisture conditions and soil aeration affect the amount and properties of macropores [61]. Tillage of very dry soil could also lead to lower stability and differing sizes and arrangement of soil aggregates.…”
Section: Tension Infiltration Experimentsmentioning
confidence: 99%